1982
DOI: 10.1677/joe.0.0950283
|View full text |Cite
|
Sign up to set email alerts
|

A study of carbohydrate metabolism in 'delayed' and 'activated' mouse blastocyst and uterus

Abstract: Several regulatory enzymes of carbohydrate metabolism were studied in blastocysts and uteri of mice in which implantation had been delayed and of oestrogen-activated mice, and compared with those of normal mice just before implantation on day 4 of pregnancy. A significant increase in the activities of phosphofructokinase and pyruvate kinase was observed but the level of lactate dehydrogenase declined in delayed blastocysts. Carbohydrate metabolism in the uterus remained essentially unchanged during the delay p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…As found by Weitlauf & Kiessling (1980), our results show that metabolic activation in vitro is not accompanied by an increase in cell numbers, while activation in utero resulted in a significantly higher number of blastomeres. Our earlier study (Sakhuja et al, 1982) had shown that dormant blastocysts exhibited significantly higher levels of PFK and PK, in comparison to normal implanting or delayed and activated blastocysts. We have now observed that within 6 h after activation in utero and in vitro there was a sharp decline in PFK and PK levels and, thereafter, steady states were maintained during the next 18 h, the levels at this time being similar to those found in normally implanting embryos.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As found by Weitlauf & Kiessling (1980), our results show that metabolic activation in vitro is not accompanied by an increase in cell numbers, while activation in utero resulted in a significantly higher number of blastomeres. Our earlier study (Sakhuja et al, 1982) had shown that dormant blastocysts exhibited significantly higher levels of PFK and PK, in comparison to normal implanting or delayed and activated blastocysts. We have now observed that within 6 h after activation in utero and in vitro there was a sharp decline in PFK and PK levels and, thereafter, steady states were maintained during the next 18 h, the levels at this time being similar to those found in normally implanting embryos.…”
Section: Discussionmentioning
confidence: 89%
“…Studies on carbohydrate metabolism during delay of implantation suggest that there is a depression of metabolic functions in the quiescent blastocyst, with reduced C02 output (Menke & McLaren, 1970) and oxygen consumption (Nilsson, Magnusson, Widehn & Hillensjo, 1982). Nevertheless, there are elevated levels of phosphofructokinase, pyruvate kinase and low lactate dehydrogenase in delayed mouse blastocysts, which returned to normal preimplantation levels upon activation with oestradiol-17ß (Sakhuja, Sengupta & Manchanda, 1982). It is not clear whether this represents heightened function of glycolysis in the delayed blastocysts or whether the enzymes showed high levels but may not have been in an active state.…”
Section: Introductionmentioning
confidence: 99%
“…Lacto-N-Fucopentaose-1, a possible ligand of galectin-1 (Sparrow et al, 1987), is found on the surface of the uterine epithelium, when it becomes more abundant and restricted to specific areas immediately prior to implantation (Lindenberg et al, 1988). The levels of galectin-1 mRNA during pseudopregnant or delay of implantation were compatible with carbohydrate metabolism in the uterus which remained essentially unchanged during the delay period (Sakhuja et al, 1982). In addition, the secreted galectin-1 in the uterine lumen may bind a galactosecontaining cell surface epitope present on the embryonic surface.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, glucose uptake remains basal until 16 h, but increases thereafter after activation of dormant blastocysts (14), suggesting that pyruvate is a major source of energy during the early stages of blastocyst activation. In contrast, evidence showing increased activity of phosphofructokinase and pyruvate kinase with decreased lactate dehydrogenase activity in dormant blastocysts (20) suggests that energy requirement during blastocyst activation is glucose dependent. Our results of significant increases in Pfkl (phosphofructokinase, liver, B-type), Eno1 (enolase 1␣, nonneuron), Pgk1 (phosphoglycerate kinase 1), Pkm2 (pyruvate kinase, muscle), and Ldh1 (lactate dehydrogenase 1, A chain) in activated blastocysts suggest that increased energy requirements during activation are satisfied by both glucose and pyruvate energy pathways.…”
Section: Carbohydrate Metabolic and Energy Pathways Are Differentiallymentioning
confidence: 93%